2018
DOI: 10.1155/2018/2856063
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin and Morin Attenuate Oxidative Stress, Mitochondrial Dysfunction, and Neurocytotoxicity, Induced by Amyloid Beta Oligomers

Abstract: Amyloid beta- (Aβ-) mediated ROS overproduction disrupts intraneuronal redox balance and exacerbates mitochondrial dysfunction which leads to neuronal injury. Polyphenols have been investigated as therapeutic agents that promote neuroprotective effects in experimental models of brain injury and neurodegenerative diseases. The aim of this study was to identify the neuroprotective effects of morin and mangiferin against Aβ oligomers in cultured cortical neurons and organotypic slices as well as their mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 52 publications
2
47
1
Order By: Relevance
“…Here, we analyzed spine dynamics, i.e., change in spine shapes and the appearance or loss of spines over time in living cell cultures. Accordingly, we observed that soluble forms of Aβ peptide or Aβ oligomers, as the active components (Alberdi et al, 2018), modulated spine dynamics within a very short-term time window. Overall, most dendritic spines were highly stable under basal conditions, whereas after treatment with Aβ oligomer stubby and mushroom spines showed the most dynamic the most dynamic behavior.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Here, we analyzed spine dynamics, i.e., change in spine shapes and the appearance or loss of spines over time in living cell cultures. Accordingly, we observed that soluble forms of Aβ peptide or Aβ oligomers, as the active components (Alberdi et al, 2018), modulated spine dynamics within a very short-term time window. Overall, most dendritic spines were highly stable under basal conditions, whereas after treatment with Aβ oligomer stubby and mushroom spines showed the most dynamic the most dynamic behavior.…”
Section: Discussionmentioning
confidence: 90%
“…Soluble oligomeric Aβ 1-42 was prepared as reported previously (Dahlgren et al, 2002;Alberdi et al, 2010Alberdi et al, , 2018. Briefly, Aβ 1-42 (Bachem, Bubendorf, Switzerland) was initially dissolved to 1 mM in hexafluoroisopropanol (Sigma-Aldrich, Saint Louis, MO, USA) and distributed into aliquots in sterile microcentrifuge tubes.…”
Section: Preparation Of Soluble Oligomeric Aβ 1-42mentioning
confidence: 99%
“…Many studies have evidenced that both phytoconstituents of DM extract, mangiferin and epicatechin, possessed neuroprotective and antiapoptotic effects in vitro and in vivo. Mangiferin protected against oxidative stress, mitochondrial dysfunction, and apoptosis caused by 6-OHDA, rotenone, MPTP, amyloid beta oligomers and subarachnoid hemorrhage [ 28 , 29 , 30 , 31 , 32 ]. Epicatechin also had neuroprotective effects against 6-OHDA-induced striatal or amyloid 25-35-induced hippocampal oxidative stress [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and mitochondrial apoptosis have long been implicated in a variety of neurodegenerative disorders, such as Alzheimer's disease (AD), Parkinson's disease (PD), and stroke (Zhang J. et al, 2017;Alberdi et al, 2018;Dai et al, 2018). The mechanism underlying aluminum neurotoxicity is poorly understood, but damage to the mitochondria and production of ROS are considered key contributors to aluminuminduced neurodegenerative disease (Leuner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%